Innovaatiotoiminta: Näkemyksiä ympäristö- ja energia-alaan - Jari Hyvärinen (The Research Institute of the Finnish Economy (ETLA), 2011)
– This study examines structures at the environment and energy sectors and those challenges to face in ongoing climate change. It investigates firstly goals behind steps how to decrease effects of climate change, research results and scenarios and which support to achieve these goals. Study also clarifies those goals set in Finland which improve environmental conditions, and moreover in the Baltic Sea. In the end, the study explores markets, business possibilities, investments and resources at the environment and energy sectors, and especially at the renewable energy sector globally and in Finland.
Keywords: H23; O13; O33; O44; 330; Global warming; environment; energy; renewable energy; innovation activity